International Trade and Inequality: A Comparative Study Between Czech Republic and Poland - Reskiyah, Emy Sri (Jurnal Ilmiah Hubungan Internasional, 2023)
Income inequality as one of the dimensions of economic inequality has been a serious social problem both in developed and developing countries. It also attracts attention both in popular and academic writing and in public debates. One of the arguments shows that trade liberalisation is linked to an increase in income inequality in high-income countries, and reduces inequality in low-income countries. The Czech Republic and Poland, as among the high-income countries, have not seen rising levels of income inequality during the financial crisis in 2008-2009 and are also among the lowest levels of income inequality. This research uses the theory of international trade and the concept of income inequality as an analytical tool. The objective of this research is to examine the reason for why both countries have not seen rising in their level of income inequality during the financial crisis in 2008-2009 and to further investigate the relations between international trade and level of income inequality by using comparative analysis and the quantitative methods of descriptive statistical analysis. This paper shows that besides a decrease in trade turnover that leads to a lower level of income inequality when it is measured by Gini Coefficient, the macroeconomic policies also play crucial part in low level of income inequality in the Czech Republic and Poland. Keywords: International Trade; Income Inequality; Poland; Czech Republic; Gini Coefficient